Decorated carbon nanofibers with mixed nickel−manganese carbides for methanol electro-oxidation in alkaline solution. (3rd February 2021) - Abbas, Mohamed; Abdel Hameed, R.M.; Al-Enizi, Abdullah M.; Thamer, Badr M.; Yousef, Ayman; El-Newehy, Mohamed H.
Abstract: Transition metal carbides were recently investigated in many vital applications due to their satisfactory thermal, mechanical and chemical characteristics. They showed a metallic architecture of the host lattice containing interstitial voids of carbon atoms. In this work, mixed nickel-manganese carbides were synthesized onto carbon nanofibers [NiC–MnC@CNFs] in different proportions using the electrospinning process with subsequent calcination at 800 °C. Scanning electron microscopy (SEM), X-ray diffraction (XRD) and Fourier transform infrared (FTIR) were employed to physically characterize the prepared nanomaterials. Homogeneous distribution of nanometallic particles over CNFs was clearly observed in SEM images. XRD charts detected the formation of mixed metallic carbides of Ni0.98 C0.02 and (Mn9 C)0.4 formulations in different nanomaterials. Excellent electrocatalytic behavior was displayed by NiC–MnC@CNFs nanocatalysts when methanol molecules were introduced into the alkaline solution. Methanol oxidation current density of 110.34 mA cm −2 was measured at the nanomaterial containing NiAc:MnAc ratio of 90:10 with a lowered Eonset value of 310 mV (Ag/AgCl). The effect of varying methanol concentration and the scan rate during the electro-oxidation reaction on the resultant nanomaterial activity was studied. Moreover, the feasibility of charge transfer step was significantly affected by the chosen potential value. Highly pronounced rate was measured at 450 mV. The chronoamperometric study revealed a promising stability trend with increased steady state oxidation current densities especially at nanopowders with lowered MnAc wt.%. The synergistic effect between mixed metallic carbides and CNFs could account for the improved electrocatalytic properties towards methanol molecules oxidation. Graphical abstract: Image 1 Highlights: Electrospinning technique was proposed to fabricate NiC-MnC@CNFs nanocatalysts. Mixed carbides nanocatalyst showed superior activity for methanol oxidation. Altering NiAc:MnAc ratios into the nanocatalyst structure affected its activity.